2012
DOI: 10.1026/0049-8637/a000045
|View full text |Cite
|
Sign up to set email alerts
|

Verarbeitung von konkreten und abstrakten Wörtern bei Kindern im Schulalter

Abstract: Zusammenfassung. Die Verarbeitung abstrakter Begriffe ist ein wichtiger Bestandteil der sprachlichen und kognitiven Entwicklung, der gerade in der späteren Kindheit relevant ist. In der vorliegenden Studie wurde ein Reaktionszeitexperiment zum lexikalischen Entscheiden über konkrete und abstrakte Nomen durchgeführt, an dem je 20 Kinder im Alter von acht bzw. zwölf Jahren sowie Erwachsene teilnahmen. Die Ergebnisse zeigen, dass Qualität und Geschwindigkeit der Wortverarbeitung in Abhängigkeit vom Alter und vom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In line with previous word processing studies with children (e.g., Silk et al, 2009 ; Kauschke et al, 2012 ), we expect an age-dependent improvement of word processing skills, reflected in higher accuracy and lower reaction times with increasing age in both tasks. Beyond this expectable age-related improvement we aim at investigating whether developmental changes occur in a linear or in a graded, stepwise manner during childhood.…”
Section: Introductionsupporting
confidence: 86%
“…In line with previous word processing studies with children (e.g., Silk et al, 2009 ; Kauschke et al, 2012 ), we expect an age-dependent improvement of word processing skills, reflected in higher accuracy and lower reaction times with increasing age in both tasks. Beyond this expectable age-related improvement we aim at investigating whether developmental changes occur in a linear or in a graded, stepwise manner during childhood.…”
Section: Introductionsupporting
confidence: 86%
“…Although Russell and Ridgeway (1983, p. 802) showed that “children seem to organize emotion terms in much the same way as do adults” across the dimensions of valence and arousal, Widen and Russell (2008) concluded that emotion categories develop gradually, having investigated the comprehension, categorization, and production of emotion terms in preschoolers. Kauschke et al (2012) showed improvements in the processing of abstract terms (including emotion words) using a lexical decision task with children between 8 and 12 years of age. Baron-Cohen et al (2010) reported substantial changes in the size of the receptive emotion vocabulary between 4 and 11 years of age.…”
Section: Introductionmentioning
confidence: 99%